Investigation into implementing a massively parallel sequencing workflow for forensic human identification in South Africa - Martin, Donna-Lee (Department of Pathology, 2025)
South Africa faces grave challenges with high crime rates and associated unidentified bodies each year. DNA profiling using capillary electrophoresis (CE) is typically utilised for human identification purposes but is limiting when applied to degraded post-mortem samples. The ForenSeqTM DNA Signature Prep kit was the first massively parallel sequencing (MPS) workflow validated on the MiSeq FGxTM system, addressing several challenges identified in CE-based methods. With forensic laboratories in developing regions showing proclivity towards a seemingly impossible adoption of MPS, sequence-based studies in Africa are sorely needed to leverage emerging advancements for forensic human identification. This study proposed a four-phased approach for laboratories to facilitate the implementation of MPS for forensic human identification, and included: optimisation, population data generation, internal validation and demonstration of applicability. An optimisation study was carried out to ensure high first-time success rates of analysing reference samples (crude buccal swab lysates) with the ForenSeqTM DNA Signature Prep kit. This entailed systematic adjustments to a direct PCR approach and the development of a lysate purification method. This optimised approach was subsequently used to conduct a population study comprising 463 consenting South African volunteers, wherein the first sequence-based allele frequency data pertaining to autosomal short tandem repeat (A-STR) markers were generated for South African populations. Rich variation was observed, where 80 novel allele sequences were recorded. An increase of 86% was observed in length- to sequence-based allele counts across several A-STR markers, with additional variation recorded in flanking regions. Furthermore, a concordance rate exceeding 99% was achieved. The novel findings and abundance of variation observed in the South African population surpasses that which has been previously characterised on a global scale, warranting further research into characterising sequence data for other forensically relevant markers. The final facet of this study involved the internal validation of the optimised MPS workflow, from sample preparation to sequencing. The workflow was deemed fit for purpose and reported the first performance parameters for post-mortem crude buccal swab lysates. The validated workflow was then applied to a forensic cold case to generate investigative leads from a severely decomposed body, demonstrating the comprehensive capability of the workflow. The synthesis of results obtained in this study have led to key recommendations for under-resourced laboratories to maximise resources for large-scale studies.